Functions and mechanisms of microglia/macrophages in neuroinflammation and neurogenesis after stroke. (July 2016) - Xiong, Xiao-Yi; Liu, Liang; Yang, Qing-Wu
Highlights: We discuss microglial and macrophage morphologies and phenotypic changes in response to acute brain damage and repair in the context of stroke. We argue that future translational studies should be targeting multiple key regulating molecules with a concept of "therapeutic time window". We suggest that constructing new experimental stroke models should be considered. We suggest that identifying new gene signatures for circulating immune cells when they enter into the CNS should be considered. We suggest that exploring the endogenous neuroprotective mechanisms responsible for brain repair should be considered. Abstract: Microglia/macrophages are the major immune cells involved in the defence against brain damage. Their morphology and functional changes are correlated with the release of danger signals induced by stroke. These cells are normally responsible for clearing away dead neural cells and restoring neuronal functions. However, when excessively activated by the damage-associated molecular patterns following stroke, they can produce a large number of proinflammatory cytokines that can disrupt neural cells and the blood-brain barrier and influence neurogenesis. These effects indicate the important roles of microglia/macrophages in the pathophysiological processes of stroke. However, the modifiable and adaptable nature of microglia/macrophages may also be beneficial for brain repair and not just result in damage. These distinct roles may be attributed to the different microglia/macrophage phenotypes because the M1 population is mainly destructive, while the M2 population is neuroprotective. Additionally, different gene expression signature changes in microglia/macrophages have been found in diverse inflammatory milieus. These biofunctional features enable dual roles for microglia/macrophages in brain damage and repair. Currently, it is thought that the proper inflammatory milieu may provide a suitable microenvironment for neurogenesis; however, detailed mechanisms underlying the inflammatory responses that initiate or inhibit neurogenesis remain unknown. This review summarizes recent progress concerning the mechanisms involved in brain damage, repair and regeneration related to microglia/macrophage activation and phenotype transition after stroke. We also argue that future translational studies should be targeting multiple key regulating molecules to improve brain repair, which should be accompanied by the concept of a "therapeutic time window" for sequential therapies.